Strategi Peningkatan Kinerja Manajemen Rantai Pasokan Jeruk Siam Di Kelompok Tani Gunung Mekar Kabupaten Gianyar - I Made Sucipta; I Wayan Widia; I Made Supartha Utama (Jurnal BETA (Biosistem dan Teknik Pertanian), 2016)
Siam citrus (Citrus nobilis var. microcarpa) is one of Bali's main commodities. However, the fact showed that agribusiness system of Siam citrus is not profitable enough for small scale farmers group. This research aimed to; (1) acknowledge the structure, mechanisms, and the systematic supply chain of Siam citrus in the Gunung Mekar Farmers Group of Gianyar Regency; and (2) know the priorities recommendations in order to increased supply chains performance of Siam citrus. This research study consisted of two stages, and each process required different respondents and analysis tools as well. The first stage (to know the structure,mechanisms, and systematic of the supply chain) is using the descriptive qualitative analysis, and the second stage (to know the recommendation priorities) is using the Analytical Hierarchy Process method (AHP) as the analysis tool. The sampling on farmer levels conducted purposively and the next sampling level determined by snowball sampling method. The research resulted three distribution patterns of Siam citrus with traditional supply chain mechanism basic. The improvement of performance supply chain management on Siam citrus, information accessibility improvement, alternative reliability, and performance indicator ofproduct quality became the most important priority